2021
DOI: 10.3389/fpsyg.2020.582805
|View full text |Cite
|
Sign up to set email alerts
|

A Constructivist Intervention Program for the Improvement of Mathematical Performance Based on Empiric Developmental Results (PEIM)

Abstract: Teaching mathematics and improving mathematics competence are pending subjects within our educational system. The PEIM (Programa Evolutivo Instruccional para Matemáticas), a constructivist intervention program for the improvement of mathematical performance, affects the different agents involved in math learning, guaranteeing a significant improvement in students’ performance. The program is based on the following pillars: (a) students become the main agents of their learning by constructing their own knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 45 publications
3
9
0
Order By: Relevance
“…Various studies on how the linguistic structure of a problem can favor or block the resolution of the problem by the students makes clear the extraordinary relationship between language and resolution of verbal problems (Carpenter and Moser, 1984;Verschaffel et al, 2000;Bermejo et al, 2002Bermejo et al, , 2021.…”
Section: Mathematics and Languagementioning
confidence: 99%
“…Various studies on how the linguistic structure of a problem can favor or block the resolution of the problem by the students makes clear the extraordinary relationship between language and resolution of verbal problems (Carpenter and Moser, 1984;Verschaffel et al, 2000;Bermejo et al, 2002Bermejo et al, , 2021.…”
Section: Mathematics and Languagementioning
confidence: 99%
“…At the same time, the student must create a model of the problem situation, that is, the mental representation that will later allow him to move onto the next decision-making stage. This can be seen in those constructivist intervention processes in which the child creates and invents his own problem-solving strategies [43].…”
Section: Problem Solvingmentioning
confidence: 99%
“…In learning progression responsive curriculum, it is expected that the sequence of contents be appropriate for students' developmental stage, age, and grade level. In addition, contents in a given curriculum is said to be appropriate if it is presented by considering the sense; from simple to complex, spiral, whole to part, children experience and real life condition, and order of events (Bermejo, Ester, & Morales, 2021;Sáez et al, 2013). The findings from this study indicated that the presentation of contents in early grade mathematics curriculum lacked appropriateness in relation to these lucidities.…”
Section: Appropriateness Of Contentsmentioning
confidence: 99%